Фазові рівноваги у системі CdSe–CdTe - Лавринюк, Зоряна Володимирівна; Змій, Ольга Федорівна; Lavryniuk, Zoriana V.; Zmii, Olha F. (Волинський державний університет імені Лесі Українки, 2007)
За результатами ДТА та РФА уточнено діаграму стану системи CdSe–CdTe. Ця діаграма є перитектичного типу. Підтверджено існування обмеженої розчинності між компонентами. The phase diagram of the CdSe–CdTe system has been detailed using the methods of differential thermal, X-ray phase analysis. The diagram corresponds to the peritectic type. The existence of the limited solid solutions on the basis of binary compounds has been established.
The Phase Diagram of the CdSe–CdTe.
Keywords: халькогенідні напівпровідники; фазова діаграма; кристалічна структура; chalcogenide semiconductors; the phase diagrams; crystal structure